DYSTOCIA DUE TO FETAL ANASARCA WITH NORMAL LIVE FETUS IN CO-LATERAL UTERINE HORNS IN A LABRADOR BITCH– A CASE REPORT - SINGH, GYAN; YADAV, RISHIPAL; KUMAR, SANDEEP; YADAV, VINAY; KUMAR, GAURAV (The Indian Journal of Animal Reproduction, 2023)
An eighteen months old Labrador bitch was presented with history of dystocia for twelve hours after whelping a dead pup. Administration of oxytocin and calcium gluconate by field veterinarian failed to relive the dystocia. Ultrasonography revealed presence of two live fetuses in the uterus and one dead fetus in the birth canal. Hence, caesarean section was performed under general anaesthesia and one dead anasarca fetus along with two live fetuses was delivered.